DELTAIC, MIXED AND TURBIDITE SEDIMENTATION OF ANCIENT FORELAND BASINS - Mutti E.; Tinterri R.; Benevelli G.; Biase D.D.; Cavanna G. (My University, 2003)
The marine fill of ancient foreland basins is primarily recorded by depositional systems consisting of facies and facies associations deposited by a variety of sediment gravity flows in shallow-marine, slope and basinal settings. Tectonism and climate were apparently the main factors controlling the sediment supply, accommodation and depositional style of these systems. In marginal deltaic systems, sedimentation is dominated by flood-generated hyperpycnal flows that build up impressive accumulations of graded sandstone beds in front of relatively small high-gradient fan-deltas and river deltas. During periods of tectonically forced lowstands of sealevel, these systems may commonly shift basinward to shelfal and slope regions. Instability along the edges of these lowstand deltas and sand-laden hyperpycnal flows generate immature and coarse-grained turbidite systems commonly confined within structural depressions and generally encased in distal delta-front and prodeltaic deposits. Because of the close vertical and lateral stratigraphic relations between deltaic and turbidite-like facies, these marginal systems are herein termed 'mixed depositional systems'. They are very common in the fill of foreland basins and represent the natural link between deltaic and basinal turbidite sedimentation.Basinal turbidite systems form in deeper water elongate highly subsiding troughs (foredeeps) that developed in front of advancing thrust systems. The impressive volumes of sheet-sandstones that form the fill of these troughs suggest that basinal turbidite systems are likely to form following periods of dramatic tectonic uplift of adjacent orogenic wedges and related high-amplitude tectonically-forced sealevel lowstands. In such deep basinal settings, sediment flux to the sea is dramatically increased by newly formed sediment in fluvial drainage basins and the subaerial and submarine erosion of falling-sealevel deltaic deposits generated during the uplift. Turbidity currents are very likely to be mainly triggered by floods, via hyperpycnal flows and related sediment failures, but can fully develop only in large-scale erosional conduits after a phase of catastrophic acceleration and ensuing bulking produced by bed erosion. This process leads to deepening and widening of the conduits and the formation of large-volume highly efficient bipartite currents whose energy dissipation is substantially reduced by the narrow and elongate basin geometry. These currents can thus carry their sediment load over considerable distances down the basin axis.
Keywords: FORELAND BASIN; MARGINAL DELTAIC AND TURBIDITE SEDIMENTATION; BASINAL TURBIDITE SEDIMENTATION